2013
DOI: 10.1002/ejoc.201300334
|View full text |Cite
|
Sign up to set email alerts
|

An Aerobic and Very Fast Pd/C‐Catalyzed Ligand‐Free and Aqueous Suzuki Reaction Under Mild Conditions

Abstract: An aerobic, ligand‐free Suzuki reaction catalyzed by Pd/C in aqueous media has been developed. This method is a very simple, efficient and mild protocol for the cross‐coupling of aryl bromides with arylboronic acids, and the reactions proceeded smoothly in excellent yields within short reaction times. Control experiments demonstrated that the Pd/C‐catalyzed Suzuki reaction was much quicker when performed in air or oxygen than in nitrogen. Furthermore, this protocol could be used for the synthesis of fluorinate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(12 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…Several groups have reported its use for Suzuki couplings using generally 10-50 mequiv. of supported palladium 54,55 . It is noteworthy that the activity of the Pd/C catalyst is often dependent on its commercial source 56,57 and that 55 decreases of the yields obtained after several reuses are frequently observed owing to the formation and/or growth of palladium aggregates 58,59 .…”
Section: A Introductionmentioning
confidence: 99%
“…Several groups have reported its use for Suzuki couplings using generally 10-50 mequiv. of supported palladium 54,55 . It is noteworthy that the activity of the Pd/C catalyst is often dependent on its commercial source 56,57 and that 55 decreases of the yields obtained after several reuses are frequently observed owing to the formation and/or growth of palladium aggregates 58,59 .…”
Section: A Introductionmentioning
confidence: 99%
“…This latter group further indicated that the oxidative addition of aryl bromides or aryl borates was the main cause for Pd leaching. Further interesting examples of Suzuki–Miyaura reactions catalyzed by Pd/C have been reported, but most developed protocols mainly focus on using active aryl halides, such as aryl iodides and bromides, to obtain non‐heterobiaryl compounds. It is still a challenge, however, to use Pd/C as catalyst for the synthesis of heterocyclic biaryl derivatives.…”
Section: Applications Of Pd/cmentioning
confidence: 99%
“…11 ). In comparison with Pd/C materials 48 49 (entry 17 and 18), Pd@Y-DDQ required less catalyst-loading and showed higher reaction yeilds. The high catalytic activity of Suzuki-Miyaura cross-coupling reaction should be attributed to the exposed and well-dispersed Pd NPs on the MOF support.…”
Section: Resultsmentioning
confidence: 98%